Buckwheat – enriched instant porridge improves lipid profile and reduces inflammation in participants with mild to moderate hypercholesterolemia. (September 2017) - Mišan, Aleksandra; Petelin, Ana; Stubelj, Mojca; Mandić, Anamarija; Šimurina, Olivera; Pojić, Milica; Milovanović, Ivan; Jakus, Tadeja; Filipčev, Bojana; Jenko Pražnikar, Zala
Highlights: Instant buckwheat-enriched porridge with health benefits was developed. Instant buckwheat-enriched porridge is effective in improving lipid profile. Instant buckwheat-enriched porridge is effective in reducing inflammation. Besides exerting health effects, the enriched porridge offers convenience in use. Abstract: Buckwheat (BW) has attracted increasing attention as an important functional food because of its beneficial effects on health. Therefore, three different instant porridges were developed: BW – enriched high-protein (A), corn-based high-protein (B) and corn-based non-protein (C), and their effects on selected clinical markers were investigated. A randomised, cross-over intervention study was performed among 34 participants with mild to moderate hypercholesterolemia. Intake of porridge A significantly reduced serum levels of total cholesterol, LDL cholesterol, triacylglycerol and, uric acid and, significantly increased serum adiponectin levels, HDL cholesterol, and fat-free mass. In conclusion, the intake of porridge A as a functional food may improve lipid profile and may reduce inflammation. These findings may support the view that consuming BW as an element in porridge is an effective and convenient nutritional therapy for improving metabolic parameters in participants with metabolic syndrome components.